NUMERICAL INVESTIGATIONS OF THE NATURAL FREQUENCIES AND MODE SHAPES OF THE TORSIONAL VIBRATIONS IN THE SAW UNIT OF A KIND OF WOOD SHAPERS, USED IN THE WOOD PRODUCTION - Vukov, Georgi; Slavov, Valentin; Kovachev, Georgi; Vlasev, Vasil (Innovation in Woodworking Industry and Engineering design, 2013)
Some numerical investigations of the natural frequencies and mode shapes of the wood shaper’s saw unit are presented in this study. These researches are done on the base of a concrete mechanic-mathematical model for investigation of free torsional vibrations of a wood shaper’s saw developed by the authors. The main features in the construction of these kind wood shapers are rendered an account of this model. The two most commonly used driving mechanisms are modeled – with a wedge belt and with a ribbed belt. The studies allow a comparison of the vibration behavior of the mechanism for both drives. The results of this study allow the determination of the resonant work regimes. The exactly determination of these regimes is important for introduction of adequate measures which can guarantee their using. The investigation`s results can be used as a base for making some recommendations concerning the increase of reliability of the wood shapers as well as the accuracy and quality of their production.